1292 Anicteric hepatitis, a rare extraintestinal manifestation following Campylobacter infection -a case study. (17th August 2022) - ,; Dayasiri, Kavinda; Anand, Geetha
Abstract : Aims: Introduction: Campylobacter infection is not uncommon in children, and extraintestinal manifestations following Campylobacter is a recognized entity, although hepatitis is rare. We present a case of anicteric hepatitis associated with Campylobacter infection in a 13-year-old boy Methods: Case Study A previously healthy 13-year-old boy was admitted to the paediatric department with a 4-day history of fever and crampy abdominal pain which was localized to the right upper quadrant. He reported loss of appetite and nausea. He was not encephalopathic. His clinical examination was unremarkable, except for diffuse tenderness on deep palpation of the abdomen, especially of the right upper quadrant. His stools were normal initially but 48 hours after admission he developed severe diarrhoea. Results: He had elevated alanine transaminase (ALT) level (181 IU/L) on admission. The full blood count showed elevated white cell count with neutrophil leukocytosis, and C-reactive protein level was high (196mg/L). His prothrombin time (PT) and activated partial thromboplastin time (APTT) were within normal limits. The faecal molecular assay detected presence of Campylobacter by polymerase chain reaction (PCR). It did not identify any other organism. The viral hepatitis (Hepatitis A IgM, Hepatitis B surface antigen, Hepatitis C IgM, Hepatitis E IgM, and IgG) panel, Epstein-Barr virus (IgG for nuclear antigen, IgM, and IgG for viral capsid antigen), Cytomegalovirus (IgM and IgG) and Parvovirus B19 (IgM and IgG) screening were negative. Pandemic corona virus was not detected on PCR testing. The auto-antibody panel for autoimmune hepatitis (Anti-nuclear antibody, Anti-smooth muscle antibody, Anti-mitochondrial antibody, Liver kidney microsomal antibody) were normal. The ceruloplasmin level and Alpha-1 anti-trypsin levels were not low. The ultrasound scan of the abdomen revealed normal hepatic architecture, making a chronic liver disease less likely. An alternative explanation for high transaminases were not found. He improved clinically within a week and his liver functions continued to improve. Conclusion: Discussion: Campylobacter infection has been associated with extra-intestinal manifestations like Guillain-Barre Syndrome, pancreatitis, erythema nodosum, haemolytic uremic syndrome, thrombotic thrombocytopenic purpura, haemolytic anaemia, glomerular nephritis, and reactive arthritis. Hepatitis is a rare complication of Campylobacter infection and is rarely reported in medical literature.